Alternative Admissible Biased Estimators - Cernuschi Frias, Bruno (2013)
In this work, a biased estimator obtained from an affine transformation of an unbiased estimator will be analyzed. In particular, the method proposed by Y. C. Eldar will be studied, and alternative approaches will be developed for the construction of biased estimators through transformations of unbiased ones. It is finally shown through simulations, that both estimators proposed in this work perform better than other estimators analyzed.